(3GdCUhd GdcHjQs - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s
(3ChdgG (B:s
(3bGd GdaGVd GHf hMTjI QMeg Gddg ai CUhdg GdcHjQ ai CHhGH JcdjS GdCLSGO hZjQgG s
(3BNQgG (B:s
(3hgPg Led ai GdMjhGf hGdeYOf GNJUQJgG hGSJhajJgG eY GdGNJUGQ HdG JWhjd hdG GNJdGW GdMb HGdHGWd hGddg JYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B155 - (3U(B156s
(3GdehLhO efg(B: (3fbhd ai GdMjhGf hGdeYOfs
(3GdfSNI HgG MhGTs
(3GfXQ CjVG Qbe (B"91" (3cjejGAs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs